Sexual Violence Against Female Labour in the Perspective of Employment Law and Legal Justice - Gatot Sugiharto; Fithriatus Shalihah; Annisa Elda Octivia (Substantive Justice International Journal of Law)
This article aims to examine legal protection for workers who are victims of sexual violence in the workplace, as well as the legal implications for perpetrators of sexual violence from the perspective of Criminal and Employment Law in Indonesia. The research method used is normative research. The research results show that legal protection for workers from sexual harassment is regulated in various existing regulations. One aspect that is regulated is the right of witnesses and victims to obtain security protection for themselves and their families, as well as freedom from threats related to the testimony they give. Furthermore, the procedures for resolving cases of sexual harassment in the workplace are limited to legal sources in the form of the Employment Law, through deliberation, negotiation, and if no agreement is reached, filing a lawsuit for termination of employment. This article finds that there is still a lack of focus in highlighting the importance of legal protection for victims of sexual harassment in the workplace to ensure their safety and comfort, including knowledge of the procedures for resolving these cases, in order to achieve optimal legal justice. Focusing on a better understanding of rights and related legal procedures is essential in ensuring adequate protection for workers who are victims of sexual violence.